Meningkatkan Hasil Belajar Matematika Dengan Metode Buzz Disertai Media Lidi Pada Materi Penjumlahan Dan Pengurangan Pada Siswa Kelas II SD Negeri 024 Rambah Tahun Pelajaran 2016/2017 - Nurlaili Manam (Indonesian Journal of Basic Education, 2018)
Abstract, This classroom action research was conducted at SDN 024 Rambah in second grade of academic year 2016/2017. From the results of processing and data analysis, then from the improvement of learning has been implemented can be drawn conclusions are as follows: The process of learning penyamapain mathematics should be based on the mastery of concepts and the provision of tools for students. Thus the tool Bantu can be used at the time of teaching and learning so that it can make materials to improve the frequency of learning outcomes. Therefore, the teacher should be able to create a learning design that can be accepted by the students. This is seen from the recapitulation in the 54.17% cycle is categorized kurng and in cycle II 83.33% is categorized well